2016
DOI: 10.1021/acs.jpcb.6b07803
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Hole Burning in Cyanobacterial Photosystem I with P700 in Oxidized and Neutral States

Abstract: We explored the rich satellite hole structures emerging as a result of spectral hole burning in cyanobacterial photosystem I (PSI) and demonstrated that hole burning properties of PSI, particularly at high resolution, are strongly affected by the oxidation state of the primary donor P700, as P700 effectively quenches the excitations of the lowest-energy antenna states responsible for fluorescence. Obtaining better control of this variable will be crucial for high-resolution ensemble experiments on protein ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(61 citation statements)
references
References 65 publications
10
51
0
Order By: Relevance
“…Another suggestion is that red Chls play a role in photoprotection. It was shown that when P700 is oxidized and the RC is closed, emission from the red sites is significantly reduced, potentially minimizing the formation of Chls triplets in PSI 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Another suggestion is that red Chls play a role in photoprotection. It was shown that when P700 is oxidized and the RC is closed, emission from the red sites is significantly reduced, potentially minimizing the formation of Chls triplets in PSI 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that cyanobacterial PSI core binds red-shifted Chls (red Chls) whose energy levels are lower than P700. It has been suggested that red Chls consist of 7-11 molecules of Chl a per 96 Chl a based on the absorption spectra of PSI at cryogenic temperatures [33][34][35] . At least four Chl a clusters are necessary to explain the absorption spectrum of red Chls.…”
Section: Resultsmentioning
confidence: 99%
“…13). Several red Chl a candidates have been reported based on hole-burning analysis 33 . In the present structure, Chls a836B-a835B-a834B and a841A-a842A form two Chl a clusters, and thus can be considered as candidates for the red Chl a clusters (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2, red line). The bleach at 704 nm represents a mixture of the excited long-wavelength Chl in the LHA [41,42] and the main band of P 700 [43]. The appearance of a bleach at 690 nm was previously attributed to an ultrafast (< 100 fs) reduction of the primary electron acceptor A 0 treated as excitonically coupled dimers Chl 2A -Chl 3A and Chl 2B -Chl 3B [20] in that fraction of PS I complexes in which the special pair P 700 was directly excited in the far-red spectral region [12,13].…”
Section: Transient Absorption Changes Of Photosystem I Variantsmentioning
confidence: 99%